The Influence of Speed, Agility, and Confidence on Extracurricular Students' Football Dribbling Ability - Hidayat, Nur; Syahruddin, Syahruddin; Hudain, Muh. Adnan; Suyudi, Imam; Sudiadharma, Sudiadharma; Siswanto, Wahyu (Journal Coaching Education Sports, 2024)
This research aims to determine the influence of speed, agility, and self-confidence on ball dribbling ability. This type of research uses path analysis with endogenous variables, namely agility, flexibility, and self-confidence, and the exogenous variable is the ability to dribble the ball. The research sample was 40 male students who took part in extracurricular football activities, taken by purposive sampling. The location of this research is SMP Negeri 4 Binamu, Jeneponto Regency. Research instruments include a dribbling test, a 50m running speed test, a dodging run test, and a self-confidence questionnaire. Research data was analyzed through path analysis and testing was carried out with the help of the SPSS version 26.00 program with a significance level of 0.05. Based on the research results, show 1) there is a direct effect of speed (X1) on self-confidence (X3) (p<0.05); 2) There is a direct effect of agility (X2) on self-confidence (X3) (p<0.05); 3) There is a direct effect of speed (X1) on dribbling ability (Y) (p<0.05); 4) There is a direct effect of agility (X2) on ball dribbling ability (Y) (p<0.05); 5) There is a direct effect of self-confidence (X3) on dribbling ability (Y) (p < 0.05); 6) There is no influence of speed (X1) through confidence (X3) on dribbling ability (Y) (p>0.05); 7) There is no influence of agility (X2) through self-confidence (X3) on ball dribbling ability (Y) (p>0.05).